THE EFFECT OF ALTITUTDE ON THE PRESENCE OF PLANT SPECIES IN STANDS FOR JUNIPERUS L. PLANT SPECIES ON KOPAONIK - Vasić, Predrag; Jaksić, Tatjana; Đukić, Nikola (Bulletin of Natural Sciences Research, 2016)
In this paper we present an assessment of the altitude effect on the plant species presence in different plant communities – the species of Juniperus genus (Juniperus communis L., Juniperus oxycedrus L. and Juniperus sibirica Burgsdorf) on Kopaonik Mountain. Two juniper species (Juniperus communis and Juniperus oxycedrus) were recorded at altitudes ranging from 420 m to 1420 m, while the third species Juniperus sibirica was found at an altitude of 2100 m. It was determined that the plant communities with the presence of species of the Juniperus genus differ in botanical terms at different altitudes. It was found that there are plant species in certain communities that are present only at some altitudes, while others were present at almost all altitudes. The species of Hypericum perforatum L. is recorded in all of plant communities surveyed that proves its best adaptation to the conditions at different altitudes.